Leisure Preference For People Place At Shopping Malls In Kuala Lumpur And Petaling Jaya, Malaysia - Hamat, Sufian (2012)
shopping and leisure. In view of much effort implemented to create conducive shopping and leisure environment, the performance of shopping mall also depends on the efficiency of its facilities. For that matter, this research has focused on the facility for people to relax and engage in leisure activities termed as “People Place” determined based on anticipation that its function is one of the contributing factors to the present state of shopping mall. The research attempted to achieve three objectives: The first objective seek for people’s conviction on the needs to provide a people place at shopping mall. The second objective wanted to identify people’s preferred planning and design measures implemented in the existing people place and the third objective wanted to identify people’s preferred planning and design measures for future development of the facility. The research identified 4 shopping malls with suitable people place as case studies and adopted the quantitative approach with the use of survey interview method based on questionnaires. A total of 404 people had participated in the survey and the data were analyzed with the use of SPSS (Statistical Package for Social Science Software) aiming to uncover opinions and preference of the people. The results for objective 1 indicated that most people had preferred the provision of people place for people to rest and conduct leisure related activities. The results for objective 2 indicated the top preferred measures in the design of the existing people place were the easy recognition of the facility as public space, the overall aesthetics appearance and the high level of brightness of the place.